Advances in the Conceptualization of the Stress Process Essays in Honor of Leonard I. Pearlin - Avison, William R.; Aneshensel, Carol S.; Schieman, Scott; Wheaton, Blair; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The stress process paradigm has been one of the most dominant conceptual models of health and illness over the past three decades. The contributions to this volume chart a new course for the stress process, extending the paradigm conceptually, methodologically, and substantively. Written in honor of Leonard I. Pearlin, the leading proponent of the stress process, the contributions to this volume provide a new direction for stress process research. Featuring contributions from leading researchers, and an afterword by Leonard I. Pearlin, this comprehensive volume covers three major sections: -Conceptual and methodological extensions of the stress process -The roles of family and work in the stress process, throughout the life course - Psychosocial factors that impact health outcomes This volume will be an invaluable resource for researchers in sociology, social psychology and public health, all seeking to understand the pervasive role of stress on social disparities in health and illness.
Conceptual and Methodological Developments -- Understanding Health Disparities: The Promise of the Stress Process Model -- Compensatory Coping with Stressors -- Neighborhood as a Social Context of the Stress Process -- Suppression Effects in Social Stress Research and Their Implications for the Stress Process Model -- Stress Processes in Social Roles and Contexts: Family and Work -- Family Structure and Women$1 (Bs Lives: A Life Course Perspective -- The Stress Process Model: Some Family-Level Considerations -- Linking Early Family Adversity to Young Adult Mental Disorders -- Work, Family, and Their Intersection -- Psychosocial Concepts and Processes -- Sense of Mattering in Late Life -- It$1 (Bs Tough to Cope in Rural Mali: Financial Coping Style, Mastery, Self Confidence, and Anxiety in a Bad and Worsening Socioeconomic Environment -- Stress Valuation and the Experience of Parenting Stress in Late Life -- Stress Process Applications in Child Victimization Research -- The Evolution of the Stress Process Paradigm -- The Stress Process as a Successful Paradigm.s
Keywords: Social sciences; Quality of Life; Sociology; Quality of Life -- Research; Consciousness; Social Sciences; Sociology; Personality and Social Psychology; Quality of Life Research; Public Health/Gesundheitswesen.